Impact of Industrialization in Nigeria - Isiksal, Aliya Z.; Chimezie, Odoh John (European Scientific Journal, ESJ, 2016)
The objective of this study is to analyze the relationship between GDP, agriculture (AR), industry (ID) and services sector (SV) in Nigeria. The Johansen co-integration testing approach demonstrates a significant long-run relationship between these three variables. The results reveal that agriculture, industry and services have a significant positive relationship with GDP. The Causality results demonstrate a bidirectional causal relationship between GDP, AR, ID and SV. It is suggested therefore that it is important to develop the agricultural sector to provide the needed support to the industrial and services sectors. Such a strategy can be expected to encourage the development and economic growth of a developing country.